Price regulation in two-sided markets: Empirical evidence from debit cards - Mukharlyamov, Vladimir; Sarin, Natasha (Journal of Financial Economics, 2025)
This paper provides empirical evidence of a well-known theoretical concern that market failures in two-sided markets are hard to identify and correct. We study the reactions of banks, merchants, and consumers to Dodd-Frank’s Durbin Amendment that lowered interchange fees on debit card transactions. Banks recouped a significant portion of their losses by charging consumers for products that they previously provided for free on the subsidized side of the two-sided market. The accelerated adoption of credit cards with higher interchange fees likely diminished—if not eliminated—merchants’ savings. These effects impede the regulation’s stated objective of enhancing consumers’ welfare through lower retail prices.